EFEKTIVITAS SISTEM HUKUM PERBANKAN SYARIAH DALAM UU N0 21 TAHUN 2008 DAN DAMPAKNYA PADA PEMBANGUNAN EKONOMI - Nurani, Nina (Jurnal Ekonomi & Keuangan Islam, 2011)
Economic development cannot be separated from the legal development as the efforts to manifest national develoment. Legal development in the era of reform is the effort to perform the effectivity of national legal system covering legal substance, legal structure, and the involvement of society that has high legal awareness to support the formation of the intended national legal system.The efforts to perform the effectivity of national legal system in reaching the national development goals namely creating people’s welfare and justice based on economic democracy, the develoment of economic system based on the values of justice, togetherness, even distribution, and the usefulness in accordance with syaria principles, the government enforce the syaria banking laws in the law itself, UU No.21 Tahun 2008, with the considerations that syaria banking has specification compared to the conventional banking. According to Berkowitz and Walker, the effectivity of legal system is performed in the form of legal behavior willingly, i.e. obedience. This requires legitimacy in terms of regulating the adequate acts leading to the agreement for obedience. The constraints of UU No. 1 Tahun 2008 are that this Act (UU) has not been comprehensive on regulating the implementation of banking activities or products by means of electronic facilities as the impacts of global economy bringing to national economic development. The aforementioned legal problems require specific rules such as separately regulating.